On lower-bound traps: a framework for the analysis of monetary policy in the age of central banks - Alfonso Palacio-Vera (Levy Economics Institute of Bard College, 2006)
We present a simple theoretical framework that integrates the notion of the natural or neutral interest rate, liquidity preference theory, and the monetary policy practice by modern central banks. We claim that this theory explains the conditions under which an economy will experience an aggregate demand deficiency problem within a modern institutional setting. Contrary to the predictions of the New Consensus View in macroeconomics, the model suggests that structural factors such as a high saving rate and, especially, a low natural rate of growth increase the chances that an economy experiences an aggregate demand deficiency. Contrary to conventional wisdom, the model predicts that a fall in the NAIRU may lead to a rise in the natural interest rate, and vice versa.
Keywords: B50; E12; E24; E50; 330; Neutral interest rate; lower-bound trap; aggregate demand deficiency; natural rate of growth